Maternal Iodine Insufficiency and Excess Are Associated with Adverse Effects on Fetal Growth: A Prospective Cohort Study in Wuhan, China. Issue 11 (18th September 2018) - Chen, Renjuan; Li, Qian; Cui, Wenli; Wang, Xiaoyi; Gao, Qin; Zhong, Chunrong; Sun, Guoqiang; Chen, Xinlin; Xiong, Guoping; Yang, Xuefeng; Hao, Liping; Yang, Nianhong
Abstract: Background: Maternal iodine status has been suggested to affect birth outcomes. Few studies have focused on its effects on fetal growth during pregnancy. Objective: This study aimed to assess maternal iodine status during early pregnancy and further examine the relation between maternal iodine status and fetal growth. Methods: A total of 2087 singleton-pregnant women participating in the Tongji Maternal and Child Health Cohort study were involved. Urinary iodine concentration (UIC) and creatinine concentration were measured in spot urine samples collected in early pregnancy (<20 wk of gestation). Fetal head circumference (HC), femur length (FL), and estimated fetal weight (EFW) were evaluated by ultrasonography in each trimester. A multiple linear regression model was used to examine the association of iodine status with fetal growth characteristics, and a mixed-effects model was used to assess longitudinal effect. Results: The median UIC and iodine-to-creatinine (I/Cr) ratio were 178 μg/L and 234 μg/g, respectively. The prevalence of insufficient iodine status (I/Cr ratio <150 μg/g) was 19.8%( n  = 414), of adequate iodine status (150–249 μg/g) was 34.8% ( n  = 726), of iodine status above the requirements (250–499 μg/g) was 32.1% ( n  = 669), and of excessive iodine status (≥500 μg/g) was 13.3% ( n  = 278). Maternal iodine insufficiency was inversely associated with fetal FL in the second and third trimesters. In stratified analysis, significant interactions were found between maternal iodine status and age as well as parity (all P  < 0.05). The longitudinal analyses showed negative associations of maternal insufficient, more than adequate, or excessive iodine status with fetal growth during pregnancy (all P  < 0.05). Conclusions: In central China, maternal iodine insufficiency and excess coexisted during early pregnancy and they both adversely affected fetal growth. There is an urgent need for ongoing monitoring of iodine status among vulnerable pregnant women in order to optimize iodine nutrition during pregnancy.